Resposta do milho doce à aplicação de diferentes doses de inoculante (Azospirillum brasilense) associada à adubação nitrogenada - Numoto, Alberto Yuji (2014)
The aim of this study was to evaluate the phenotypic characteristics of sweet corn as a function of seed inoculation with Azospirillum brasilense associated with nitrogen fertilization at "Summer" Harvest of 2012/2013 and "Autumn-Winter" of 2013, in Parana Northwest. The experiments were conducted at the Experimental Farm of Iguatemi (EFI), located in the district of Iguatemi, Maringa, Parana. The experimental design was randomized complete block with treatments with four replications in a factorial 5 x 2 x 2, with 5 levels of inoculation (0, 50, 100 , 150 and 200 mL ha-1) containing Azospirillum brasilense (AbV5 and AbV6 strains), 2 levels of nitrogen fertilizer at sowing (0 and 30 kg ha-1) , two levels in coverage (0 and 110 kg ha-1) , and one simple hybrid modified (RB 6324) of group supersweet. The variables evaluated were plant height, leaf area index, leaf nitrogen content, number of rows per ear, number of kernels per row, productivity without husk, husked productivity of commercial ears, total sugar content and protein in the seeds. Statistical analysis of the data showed that inoculation with the bacterium Azospirillum brasilense positively affected the leaf area index, productivity of commercial ears husked, and the content of protein and total sugars in the grains in combination with nitrogen fertilizer on "Summer" Harvest. While in "Autumn-Winter" Harvest the response variables of leaf area index, total sugar content and yield of husked ears were positively influenced by inoculation by seed treatment. Moreover, in both growing seasons no significant effects of inoculation and nitrogen fertilization were observed in the number of kernel rows per ear and number of grains per row. Concludes that the use of Azospirillum brasilense in the treatment of sweet corn seeds can increase the net income of the farmer, since it positively affects the chemical quality of the grains and the density of ears.